Perencanaan Sistem Digitalisasi Promosi pada Objek Wisata Colo Muria Kabupaten Kudus - Mayashofa, Ira Siti; Nashiroh, Putri Khoirin (Jurnal Pendidikan Teknologi Kejuruan, 2021)
Tourism is a multidimensional activity that can show the identity of tourist attractions, one of which is the Colo Muria Tourism object which has local charm and wisdom that can be visited by tourists. This study aims to plan a digitalization system at the Colo Muria tourist attraction, Kudus Regency using Augmented Reality technology. The research method used is agile development. The steps of this research are Planning, Analysis, Design, Implementation, and Testing. Application testing using alpha testing in the form of functional testing (black box testing), portability testing and beta testing in the form of usability testing (media expert tests and application user observer tests). The alpha test that tested the functionality aspect using the black box test showed that the application was running well and as planned. Beta testing was carried out by media experts and the percentage results were 80%. From these results, it can be seen that the digitization system at the Colo Muria tourist attraction has good capabilities, so it can be declared worthy of being used as a means of tourism promotion. For beta testing using the respondent test, the final average score is 79%, so it is included in the acceptable or feasible criteria for use. Suggestions put forward for further research are to add better-animated travel videos and 3D object animations so that the Colo Muria tourism object digitization system is more complete.